Estimation of salivary cortisol level and psychological assessment in patients with oral lichen planus - Anuj Gaur; C Anand Kumar; Jyothi S Kumar; Gopa K R. Nair; Vinay M Agrawal (Wolters Kluwer Medknow Publications, 2018)
Introduction: Oral lichen planus (OLP) is a relatively prevalent chronic inflammatory disease, which affects the skin and mucous membrane. The etiology of OLP is unknown and there is controversy over the role of stress as an etiologic factor of OLP. Aim: To assess the salivary cortisol levels and psychological factors in OLP patients. Material and Methods: This study investigated the salivary cortisol level in 30 clinically and histopathologically proven OLP patient and 30 healthy individual. Salivary cortisol levels were analyzed by enzyme-linked immunosorbent assay methods. The psychological factors of study and control groups were assessed by DASS 21questionnaire (depression anxiety stress scale). Salivary cortisol levels and psychological factors were compared by using student's t-test. Results: The mean salivary cortisol level among study group was 9.90 ± 3.09 ng/dL as compared to the 6.92 ± 2.21 ng/dL of the control group with P < 0.001 which was highly significant. Study showed significantly higher stress anxiety and depression levels when compared to controls. Conclusion: Hence, it is concluded that increased salivary cortisol levels and psychological factors showed positive results in development of OLP.